4c-5d+2c-6d=

Simple and best practice solution for 4c-5d+2c-6d= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4c-5d+2c-6d= equation:


Simplifying
4c + -5d + 2c + -6d = 0

Reorder the terms:
4c + 2c + -5d + -6d = 0

Combine like terms: 4c + 2c = 6c
6c + -5d + -6d = 0

Combine like terms: -5d + -6d = -11d
6c + -11d = 0

Solving
6c + -11d = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '11d' to each side of the equation.
6c + -11d + 11d = 0 + 11d

Combine like terms: -11d + 11d = 0
6c + 0 = 0 + 11d
6c = 0 + 11d
Remove the zero:
6c = 11d

Divide each side by '6'.
c = 1.833333333d

Simplifying
c = 1.833333333d

See similar equations:

| -85=7x-8 | | 4(y+8)=0.5(4y-8) | | y+2x=40 | | 4x^3/3xy^-4 | | 0=16-3x-4y | | 13x+9=3x+9 | | -51=-2(1-5n)-(1-6m) | | x(6x-7)=o | | 5r^2-46r+48=0 | | 2q+3=11 | | 4a+2b+c=1000 | | 2x+8=2(1+2x) | | 5n^2+38n-63=0 | | -7c+4-c=-2(c+3) | | -2x(x+5)=3x-15 | | 0x+8=20 | | 4x-10=-4x | | N^2/2n-1 | | 3(3x+4)=3x+18 | | 10a=3.5(17) | | 2x+58=3(2+5x) | | 8x-(4x+7)+11=2x | | 7v^2-2v=0 | | 2a+6-6a= | | -(6m+4)=4m-2(6m+2) | | 9a+3b+c=1750 | | -4k+2(5k-6)= | | 20n^2-16n-160=0 | | -4/.75 | | 81x^2-1/16 | | 5+6y-18y= | | 3y+2y-8=17 |

Equations solver categories